EFEKTIVITAS TEKNIK EKLEKTIKDALAM MENINGKATKAN KESEHATAN MENTAL REMAJA DI PANTI ASUHAN MUHAMMADIYAH PUTRIKABUPATEN PAMEKASAN TAHUN 2018 - Siti Nurul Jannah (Bayan lin-Naas : Jurnal Dakwah Islam, 2020)
ABSTRACTTeenagers tend to have unstable psychiatric conditions, So in these teenage years, growth and development in any aspect can not always be solved by a smooth way In order to occur continuity between the body and soul, then reguire techniques that fit with problems that happened, eclectic means selecting, choosing the appropriate doctrine or method from various sources or systems. The theory of eclectic counseling refers to a systematic counseling that holds on to theoretical view and approach, which is a mixture of elements taken or selected from several conceptions and approaches.Issues raised in this problem is 1. How is the effectiveness of eclectic techniques in improving mental health of adolescents at Muhammadiyah Putri orphanage Pamekasan 2. What are the obstacles faced in improving mental health of adolescents at Muhammadiyah Putri orphanage Pamekasan.To find out more about this eclectic technique, it is necessary to use the approach with qualitative field research, while the method used is interview method, obserfvation, and documentation, from this method, then researcher and analysis to obtain data and information. The subject was taken from the board and the foster children of the orphanage Muhammadiyah 1 caretaker of 4 foster children of the orphanage, for the validity of the data, the researcher uses triangulation with two ways: comparing the observation data with the result of interview with triangulation and triangulation between methods is comparing the state and perspective of a person with various approaches and views of others.Eclectic techniques applied in the Muhammadiyah Putri orphanage Pamekasan District which combines several techniques from several theories that exist in an effort to improve the mental health of adolescents. The result of the research shows that, it is not only the counseling technique used in the effort to improve the mental health of adolescents of the orphanage but also combine with religious activities that are regularly applied in this time. And the results are quite satisfactory.Kata Kunci: Remaja, Eklektik, Mental